Analysis of the Sriwijaya Air SJ-182 Accident Factors from the OSH Perspective - Kultum Fiaunillah; Ahmad Mustofa (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2025)
This study analyzes the causes of the Sriwijaya Air SJ-182 plane crash that occurred on January 9, 2021, in the Thousand Islands area, from the perspective of Occupational Safety and Health (OSH). This qualitative study employs a literature review method, utilizing data from official reports by the National Transportation Safety Committee (KNKT), academic journals, and credible media sources. The findings reveal that the accident resulted from a combination of technical factors, such as autothrottle failure; human factors, including the crew’s unpreparedness to respond to malfunctions; and organizational factors, such as inadequate training and weak oversight. These findings indicate gaps in the implementation of OSH principles within the aviation sector. Therefore, this study highlights the importance of comprehensive OSH application in all aspects of flight operations. The proposed policy recommendations include enhancing crew training quality, conducting regular and thorough aircraft maintenance, and strengthening risk-based decision-making systems. The implementation of these measures is expected to prevent similar incidents in the future and to improve aviation safety standards in Indonesia.